Correlation Between Candidiasis And Mortality In Gastric Ulcer Perforation Patients - Faradina Sulistiyani; Vicky Sumarki Budipramana; Pepy Dwi Endraswari (HM Publisher, 2021)
Background: Gastric ulcer disease remains the most common gastrointestinal disease. This affects about 4 million people every year worldwide with an incidence of 1.5%-3% and 2-14% of these will progress to perforation. Mortality is reported in 30% of cases and caused morbidity in 50% of patients. Some studies have suggested that mortality in patients with peritonitis accompanied by candidiasis ranges from 20%-75%, whereas others have argued that the presence of fungal isolates in patients with perforated peptic ulcer does not affect the outcome. A recent study reported an incidence of 45% of patients peptic ulcer perforation cases accompanied by candidiasis in Dr. Soetomo General Hospital Surabaya in 2019.Methods: This was a cross sectional study based on medical record data of patients with gastric ulcer perforation accompanied by candidiasis who underwent laparotomy and gastric repair surgery at Dr. Soetomo General Hospital Surabaya from January 2019 to December 2020.Results: There was no significant correlation between candidiasis and mortality in gastric ulcer perforation patients (p=0.989).Conclusion: Candidiasis does not increase mortality in patients with gastric ulcer perforation.